Impact of Electoral Reforms on Nigerian Democratic Consolidation: A Historical Appraisal - Bashir, Muktar; Musa, Aminu (Tun Dr. Mahathir Mohamad Thoughts Institute (IPDM), 2018)
The paper examines the historical impact of electoral reforms on the Nigerian democratic consolidation. It is a well-known fact that the success of any liberal democratic practice across the globe in general and Nigeria in particular is largely a function of free, fair and credible election. The paper relied mainly on secondary sources in generating data. Through the data gathered from historical documents, draft of electoral laws from independence to date and the reports of the various electoral reform committees, the paper discovered that various reforms have been conducted over the years to improve the Nigerian electoral process. The electoral reforms have been either for transition (colonial to independence or military to civilian) or for consolidation (civilian to civilian). In terms of the impact of the reforms on democratic consolidation, the paper discovered that the electoral reforms did not yield any positive result from the colonial era to the Second Republic, with little improvement during the aborted Third Republic even though the election was nullified. From 1999 to 2015, the electoral reforms have improved positively on the country’s electoral process due to the introduction of technological equipment in the election process. In view of these therefore, the paper recommends that the Electoral Management Body should consolidate the electoral successes recorded in 2011 and 2015 general elections and improve upon them. The use of smart card reader for accreditation should be continued. However, accreditation and voting should be carried out simultaneously. Also, some of the challenges associated with the smart card reader should be addressed.